The contribution of mining companies to local economic development through corporate social responsiility in Kathu, Northern Cape - Ramoroka, Kago Andrew (My University, 2014)
ABSTRACT This research was conducted in a bid to understand the mining industry’s contribution to Local Economic Development (LED) through Corporate Social Responsibility (CSR) in the Northern Cape Province. The study was motivated by the apparent general criticism that is often levelled against the mining industry by various communities, labour organisations and political parties for not playing its part in terms of contributing to the socio-economic upliftment of the areas where these mining companies operate. This criticism exists despite these mining companies’ commitment to advance socio-economic transformation through Social and Labour Plans (SLP). In other words, South African mining policy dictates and compels the mining companies to show willingness as well as pledge their commitment to socio-economic transformation in areas where they intend to operate as a way of ensuring that mining activities in the country benefit the people who reside in these mining areas. This is a condition that government imposes on these companies in exchange for a licence to operate. If this is the case, then why is the mining industry, in general, accused of not playing its part in terms of contributing to socio-economic transformation in areas where there are mining operations? In order to understand this phenomenon, the research sought to understand the link between the mining companies’ CSR initiatives and the LED programmes and strategies of communities where these mining companies operate. Furthermore, in the quest to understand the relationship between CSR and LED, it was also vital to understand the relationship between key stakeholders such as government, community and mining companies in an effort to ascertain the level of partnerships in approaching LED. To this effect, CSR, LED and partnerships served as the key variables for analysis in the quest to understand the phenomenon, thereby achieving the objectives of this research. This research has revealed that there are key areas that constitute a challenge to LED. These are lack of a coordinated approach to LED, poor partnerships amongst stakeholders and weak monitoring and evaluation mechanisms from government. Although government has taken strides in formulating the policies to drive transformation in the mining industry, more still needs to be done to ensure that these policies result in the realisation of a desired state of evident socio-economically transformed mining towns. In order to deal with these challenges, the study proposes the need for a new approach to LED with specific reference to mining towns, the need for an improved and vigorous regulatory framework and the need for improved partnerships. The research presents these key factors as the possible solution to the challenges of Local Economic Development in mining towns in the Northern Cape Province.
MM Thesis 2014
Keywords: Social responsibility of business -- South Africa, Economic development -- South Africa,Mineral industries -- South Africa.